The association between methamphetamine use and number of sexual partners in men who have sex with men: a systematic review and meta-analysis - Salah Moradi; Yousef Moradi; Khaled Rahmani; Bijan Nouri; Ghobad Moradi (BMC, 2022)
Abstract Background Methamphetamine use in men who have sex with men population is significantly higher than that in the general population. Meth use can cause high-risk sexual behaviors, such as having sex with a variety of sexual partners. The aim of this study was to determine the association between meth use and the number of sexual partners in MSM. Methods Searching international databases (PubMed (Medline), Scopus, Web of Sciences, Embase (Elsevier), PsycInfo (Ovid), Cochrane CENTRAL (Ovid)) until March 2021 was performed in this meta-analysis using appropriate keywords terms to identify related articles. After retrieving articles in these databases, screening was performed based on the title, abstract and full text of the articles, and the final related studies were selected and evaluated using the Newcastle Ottawa scale checklist. Results The sample size consisted 18,455 people in this study, including four cohort studies with a sample size of 15,026 MSM and four case-control studies with a sample size of 3429 MSM. The results of meta-analysis showed that meth use increased the number of sexual partners in MSM (RR: 3.70; % 95 CI: 2.04-6.70). The results of subgroup analyze based on the number of sexual partners showed that in MSM taking meth, the risks of having one to three, four to five, and six or more than six sexual partners were respectively 2.82, 2.98 and 5.89 times higher than those in MSM who did not take meth. Conclusion The results showed that meth uses in MSM increased the number of their sexual partners. Due to the fact that increasing the number of sexual partners and high-risk sexual behaviors increase the risk of contracting sexually transmitted diseases such as HIV, it is necessary to adopt control programs to prevent meth use by this group, or to implement programs of reduction in the risk of STIs for this group.